Development and psychometric properties of sexual health literacy for adults (SHELA) questionnaire - Raziyeh Maasoumi; Mahmoud Tavousi; Fatemeh Zarei (Tehran University of Medical Sciences, 2019)
Background & Aim: Assessment of sexual health literacy requires an appropriate tool. The purpose of this study was to develop and validate a questionnaire to evaluate the level of sexual health literacy among Iranian adults. Methods & Materials: This study was designed in two phases in Tehran during 2017-2018. In the first step, the questionnaire was developed by item generation through expert panel and literature review. In the second step, the assessment of psychometric properties of the questionnaire including face, content, and structure validity (exploratory factor analysis) and convergence criterion (using general health literacy questionnaire) were done. Reliability of the questionnaire was assessed by internal consistency (Cronbach's alpha) and intraclass correlation coefficient (ICC). Data were analyzed using the SPSS software version 21. Results: The content validity indices (CVI and CVR) for all items were 0.84 and 0.81, respectively. Exploratory factor analysis identified four factors including skills of access, reading and understanding, evaluation and analysis, and application of information that explained %68.1 of the variance. Convergent validity of the questionnaire showed a correlation between the questionnaire's dimensions and general health literacy questionnaire in the range of 0.31 to 0.70. The SHELA showed a high internal consistency reliability with Cronbach's alpha, ranging from 0.84 to 0.94 and intraclass correlation coefficient (ICC), ranging from 0.90 to 0.97. Conclusion: The psychometric assessment of the 40-item questionnaire (SHELA) indicates desirable validity and reliability. This questionnaire is suggested for assessing the level of sexual health literacy of adults in future studies.